آليات الحجاج ( الوصل و الفصل) من منظور البلاغة الجديدة في الخطب المنبرية الدينية - خطبة " طرق الوقاية من وباء كورونا " للشيخ " صلاح البدير" أنموذجا - بوصبيع, وداد; حمودين, علي (جامعة الوادي - university of Eloued, 2022)
تُحاول هذه الدّراسة الوقوف على آليات البلاغة الجديدة (الوصل والفصل) و التي أرسى دعائمها الفيلسوف البلجيكي "شاييم بيرلمان"، وجعل منها ركيزة من ركائز الدّرس الحجاجي. وذلك بتطبيقها على خطبة منبرية دينية على اعتبار أنّ الخطب المنبرية وسيلة تواصلية يحتاج فيها المرسِل إلى قدر كبير من الحجج قصد إقناع الطرف الآخر. على أنّنا سنسلّط الضوء على خطبة معاصرة ألقيت في ظلّ الظروف الرّاهنة، المتمثلة في انتشار الوباء معنونة بـ:"طرق الوقاية من وباء كورونا" للشيخ "صلاح البدير". فإلى أيّ مدى وُفق الخطيب في توظيف تقنيات البلاغة الجديدة (الوصل والفصل)؟ وهل تمكّن بحق من إقناع المتلقين وإيصال مقاصده إليهم ؟. The curent study seeks to identify the mechanisms of the new rhetoric (connection and separation) that the Belgian philosopher Chaim Perelman laid its foundations and critically made it one of the pillars of the Argumentative study. By applying it to a religious tribune sermon on the grounds that the sermons are a means of communication in which the sender needs a great deal of arguments in order to persuade the other party, that we will shed light on a contemporary sermon delivered in light of the current circumstances, represented in the spread of the pandemic, entitled: “Methods of prevention from Corona pandemic "of Sheikh" Salah Al-Badir. " To what extent did the preacher succeed in employing the new techniques of rhetoric (connection and separation)? Was he truly able to convince the recipients and communicate his purposes to them?
From The Perspective Of New Rhetoric In The Religious Sermons .the Sermon Of "methods Of Prevention Of The Coronavirus Pandemic" By Sheikh "salah Al-badir" - As An Example
مقال
Keywords: آليات ; البلاغة الجديدة ; الوصل و الفصل ; الخطب المنبرية الدينية ; الحجاج; Mechanisms ; New Rhetoric ; Connection and Separation ; Tribune sermons ; Argumentations